2013
DOI: 10.1186/1742-2094-10-79
|View full text |Cite
|
Sign up to set email alerts
|

Primary blast injury-induced lesions in the retina of adult rats

Abstract: BackgroundThe effect of primary blast exposure on the brain is widely reported but its effects on the eye remains unclear. Here, we aim to examine the effects of primary blast exposure on the retina.MethodsAdult male Sprague–Dawley rats were exposed to primary blast high and low injury and sacrificed at 24 h, 72 h, and 2 weeks post injury. The retina was subjected to western analysis for vascular endothelial growth factor (VEGF), aquaporin-4 (AQP4), glutamine synthethase (GS), inducible nitric oxide synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 34 publications
0
42
0
1
Order By: Relevance
“…These studies misleadingly report results of air jet and not blast wave models. Recently, a rat study set off live explosive charges hung near the caged animals (Zou, 2013); but, while this open air approach is a very authentic blast simulation, it is highly difficult to precisely reproduce the resulting blast wave that strikes the animals due to many influential factors (e.g., air humidity, charge size / shape, surface reflections, and incidence angle). In contrast, our model here utilizes high fidelity simulated air blast waves (i.e., Friedlander waveform) as generated in an environmentally sealed shock tube to induce the injuries; and thus, produces visual system damage of a more realistic degree and time post-exposure to the human condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies misleadingly report results of air jet and not blast wave models. Recently, a rat study set off live explosive charges hung near the caged animals (Zou, 2013); but, while this open air approach is a very authentic blast simulation, it is highly difficult to precisely reproduce the resulting blast wave that strikes the animals due to many influential factors (e.g., air humidity, charge size / shape, surface reflections, and incidence angle). In contrast, our model here utilizes high fidelity simulated air blast waves (i.e., Friedlander waveform) as generated in an environmentally sealed shock tube to induce the injuries; and thus, produces visual system damage of a more realistic degree and time post-exposure to the human condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the brain visual centers are being directly affected, since it is well established that blast wave exposure causes traumatic brain injuries (Warden, 2006). Despite the difficult lifelong disability that permanent loss of vision represents, there are currently only a modest number of studies in animals that have attempted to assess blast wave injuries to the visual system (Petras, 1997;Koliatsos, 2011;HinesBeard, 2012;Jiang, 2013;Mohan, 2013;Zou, 2013;Bricker-Anthony, 2014a, b;Dutca, 2014;Wang, 2014;Bricker-Anthony, 2015;Choi, 2015). Many of these prior studies fall short on the soundness of experimental design (e.g., poor blast simulation and/or non-inclusive outcome measures); and only two have looked at potential drug treatments using agonists to the β-adrenergic receptor and nicotinamide phosphoribosyl transferase, as delivered by topical application to the cornea or systemically by intraperitoneal injection, respectively (Jiang, 2013;Dutca, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These retinal changes were sustained for up to 3 wk after the initial blast exposure, suggesting a combination of acute and chronic damage to the retina [14].…”
Section: Introductionmentioning
confidence: 90%
“…Many studies related to traumatic brain injury have been performed. This traumatic damage is caused by damage to the retinal ganglion cell, outer nuclear layer, and neuroglia, and the effects on the eye and visual system are diminished (Mohan et al, 2013;Zou et al, 2013;Wang et al, 2014). The authors found a decrease in retinal nerve fiber layer (RNFL) thickness and a decrease in pattern electroretinography (ERG) 3 to 4 months after injury, which correlated with punctate regions of reduced cellularity in the ganglionic layer and damage to the optic nerve (Mohan et al) Potentilla fulgens is an alpine plant of Western Himalayas which is consumed in all parts of the world for its promising medicinal properties.…”
Section: Introductionmentioning
confidence: 99%